(untitled) (Palíndromo, 2021)
These loose thoughts, aphorisms, listings, small daydreams, reflections, incomplete alphabet, texts were elaborated during the coronavirus quarantine from mid-March 2020. They are presented here in alphabetical order, which does not correspond to their chronology.